2011
DOI: 10.1073/pnas.1103906108
|View full text |Cite
|
Sign up to set email alerts
|

Mycosporine-like amino acids are multifunctional molecules in sea hares and their marine community

Abstract: Molecules of keystone significance are relatively rare, yet mediate a variety of interactions between organisms. They influence the distribution and abundance of species, the transfer of energy across multiple trophic levels, and thus they play significant roles in structuring ecosystems. Despite their potential importance in facilitating our understanding of ecological systems, only three molecules thus far have been proposed as molecules of keystone significance: saxitoxin and dimethyl sulfide in marine comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 54 publications
(81 reference statements)
1
30
0
1
Order By: Relevance
“…However, although MAA levels in A. tenebrosa during summer are not maximal, the levels present would still provide some degree of protection against UV-A and, considering both shinorine [72] and porphyra have been shown to have antioxidant capacity [73], potentially UV-A + UV-B induced oxidative stress. Other studies have also demonstrated that MAA levels are often not high enough throughout most of summer to completely protect DNA from UV-B damage [22,71,[74][75][76][77] and the results of these studies are consistent with our observation that CPD levels are approximately twice as high in A. tenebrosa during the summer periods, when animals were exposed to high UV-R doses, than in D. aethiops. Considering the sessile nature of A. tenebrosa, and the lack of any physical adaptations to reduce the impact of UV-R, this sea anemone will most likely require efficient mechanisms to repair DNA damage and keep CPD levels below that which could result in cell death.…”
Section: Discussionsupporting
confidence: 93%
“…However, although MAA levels in A. tenebrosa during summer are not maximal, the levels present would still provide some degree of protection against UV-A and, considering both shinorine [72] and porphyra have been shown to have antioxidant capacity [73], potentially UV-A + UV-B induced oxidative stress. Other studies have also demonstrated that MAA levels are often not high enough throughout most of summer to completely protect DNA from UV-B damage [22,71,[74][75][76][77] and the results of these studies are consistent with our observation that CPD levels are approximately twice as high in A. tenebrosa during the summer periods, when animals were exposed to high UV-R doses, than in D. aethiops. Considering the sessile nature of A. tenebrosa, and the lack of any physical adaptations to reduce the impact of UV-R, this sea anemone will most likely require efficient mechanisms to repair DNA damage and keep CPD levels below that which could result in cell death.…”
Section: Discussionsupporting
confidence: 93%
“…2, 18, 19, 32 These organisms have a fused divergent DDGS and O-MT, unlike traditional MAA gene clusters where the DDGS and O-MT are discrete. Phylogenetic analysis suggests that multiple horizontal gene transfer (HGT) events spread this fusion protein, with origins in cyanobacteria and dinoflagellates.…”
Section: Natural Distribution Of Sh7pcsmentioning
confidence: 99%
“…MAAs have features of keystone molecules, due to their presence throughout many trophic levels, yet their function differs not only by organism but also within single organisms. 32 In bacteria, production of MAAs has been associated with providing protection against UV damage, salt stress, and high ammonium due to increased MAA levels under these conditions. 22, 28, 41, 42 In the cyanobacterium Microcystis aeruginosa , shinorine was found in the slime layer, where it appears to have a primary structural role in the sheath and a limited role in UV protection.…”
Section: The Biology and Ecology Of Sh7pcs And Their Productsmentioning
confidence: 99%
“…A third mechanism is sensory inactivation, in which the ink secretion partially blocks the activity of peripheral chemoreceptors of predators and thereby affects the predators' ability to detect and respond to appetitive cues (LoveChezem et al, 2013). The ink of sea hares also contains intraspecific alarm cues that evoke escape behaviors of conspecific sea hares, thus also functioning as an antipredatory chemical defense (Fiorito and Gherardi, 1990;Kicklighter et al, 2007Kicklighter et al, , 2011. The diversity of defensive mechanisms allows sea hares to defend themselves against various species of predators (depending on the predators' sensitivity to the chemicals); against various individuals of a given species of predator (depending on the individual's physiological state, such as hunger); and in different envi-ronments (in the absence of foods containing diet-dependent chemical defenses).…”
Section: Introductionmentioning
confidence: 99%